The Impact of CSR Disclosures on Malaysia Individual Investors’ Investment Decision - Fum, Qi Teng (2021)
Corporate social responsibility (CSR) is increasingly valued as a strategic tool for sustainable business development and addressing ethical issues. However, research and understanding of CSR’s impact on Malaysian individual investors' investment decisions are limited. Thus, this paper aims to propose an exploratory study to understand individual investor's investing decisions in relation to the impact of CSR disclosures of companies in Malaysia. More precisely, this paper uses an exploratory qualitative approach to develop a ground understanding of the individual investors' evaluation of their perceptions towards a company's CSR position during the investment decision-making process, particularly in the Malaysian context. Semi-structured in-depth interviews were conducted using open-ended interview questions as the main instrument for the richer and descriptive data collection on in-depth individuals' experiences. Subsequently, the result analysis detailed the attitudes and perceptions of Malaysian individual investors towards the CSR disclosures, actual impact of CSR disclosures on the investment decision, the significance of annual reports in communicating CSR information factors that contribute to the use of the annual report for CSR information, and the types of CSR activities favoured by the Malaysian individual investors. Furthermore, this study is valuable in revealing specific issues and interests related to CSR disclosures and investment decisions that had not been previously identified in the existing research. Public listed companies in Malaysia could also consider the findings when promoting the CSR agenda or development programs that adhere to the CSR requirements set by Bursa Malaysia. Although this study is particularly suited for the Malaysian context, the outcomes could shed some light on the CSR initiative and its impacts on the individual investors’ investment decisions in other countries, since CSR adoption status in publicly listed companies overall does not significantly differ between countries.